History of the Development of Islam in Turkey - Ine Musfiroh Saniyatunisa; Hanifah Fikriani Dewi; Hafizha Aditya Putri; Iko Rizqonah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2022)
This article discusses Turkey which has developed rapidly for hundreds of years. Although the majority of the population is Muslim, Turkey has developed into a republic with a secular democracy. The history of the development of Islam in Turkey has made a country that constructs Islam as a rational religion. The first period begins with the establishment of the Ottoman empire, the second period is marked by the restoration of the empire, the third period is the ability of the Ottomans to defend their territory, the fourth period the empire subsides then progresses, the fifth period is the rise of Turkish culture and becomes a republic not based on empire, caliphate and dynasty.